Relative Amplitude Preservation Analysis on Interpolation Methods of The Unaliased F-K Trace Interpolation and Regularized Nonstationary Autoregression - Wahyu Triyoso; Sunawar Kunaifi (Scientific Contributions Oil and Gas, 2023)
The seismic data interpolation method has been widely used to increase the fold coverage in seismic data processing. This technique can be applied to convert multi-2D lines into pseudo-3D, which is an alternative to obtaining 3D seismic volume data due to the relatively high acquisition cost. However, the quality of the seismic interpolation results is not the same as the real 3D seismic data acquisition results. This study carefully analyzed these differences to understand how accurate the results were. There are two methods used for data interpolation, namely Unaliased f-k trace interpolation (UFKI) and Regularized Interpolation Nonstationary Autoregression (RNA) methods, which are applied to 2D pre-stack data to increase the fold coverage and 3D data to convert multi-2D lines into pseudo-3D. Then, the interpolation results on the pre-stack data are evaluated on the 2D and 3D data, and an amplitude change is analyzed. It is done to test whether the amplitude of the seismic data from the interpolation results is still relatively preserved based on the evaluation results of the changes in the AVO response. The results show that the interpolation process in the receiver and shot gather domain (UFKI and RNA) could increase the fold coverage and maintain the relative amplitude preservation and AVO response